Guidance And Counseling Teachers' Efforts In Overcoming Teenagers ' Smoking Behavior Through Information Services In Sidamanik Village - Dhea Aulia Putri; Lisna Marselina; Muhammad Haddad Alwi; Sylvina Febrianti; Alfin Siregar (Jurnal Multidisiplin Sahombu, 2024)
The purpose of study This is For to obtain accurate information about guidance teacher efforts counseling in overcome behavior smoking among teenagers in Sidamanik Village. Research This use method qualitative, which describes results data processing with words and pictures common occurrences in the field. Population sample in study This is teenagers in Sidamanik Village. The data collection process was carried out through method observation, interviews, and studies documentation. Research results This disclose that reason teenager smoking in Sidamanik Village is convenience in get cigarettes for sale in a way free and influence friends at school who invite they For smoking. Efforts made by guidance teachers counseling in handle behavior smoking among teenagers in Sidamanik Village covering service counseling individual who is executed very a week, counseling groups, and collaboration with parents. There are a number of obstacles faced by guidance teachers counseling, namely : first, many teachers at school are lacking understand about guidance counseling ; second, guidance teacher counseling No own timetable special For guidance counseling ; and third, there is difficulty in communicate between guidance teachers counseling and parents or guardian teenagers, so that communication No walk with fluent.